2010
DOI: 10.1111/j.1464-410x.2009.09101.x
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of neoadjuvant erlotinib in patients with muscle‐invasive bladder cancer undergoing radical cystectomy: clinical and pathological results

Abstract: The EGFR inhibitor erlotinib, when administered in the neoadjuvant setting, can have beneficial effects in terms of surgical pathology and short-term clinical outcomes in patients undergoing RC for invasive bladder cancer. Analyses are underway to examine the molecular correlates of the apparent clinical effect of neoadjuvant therapy in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(65 citation statements)
references
References 24 publications
2
60
0
3
Order By: Relevance
“…Initial studies showed great promise for the use of EGFR inhibitors in the setting of advanced bladder cancer in humans (31,32). As expected, Iressa treatment strikingly decreased levels of phosphorylated EGFR, AKT, and extracellular signal-regulated kinase (ERK; data not shown.).…”
Section: Discussionsupporting
confidence: 52%
“…Initial studies showed great promise for the use of EGFR inhibitors in the setting of advanced bladder cancer in humans (31,32). As expected, Iressa treatment strikingly decreased levels of phosphorylated EGFR, AKT, and extracellular signal-regulated kinase (ERK; data not shown.).…”
Section: Discussionsupporting
confidence: 52%
“…At a mean follow-up of 24.8 months, 50% of the patients were alive and still disease-free. This suggests that EGFR inhibition could be beneficial for some patients with mUC but that, for reasons still not understood, resistance to EGFR inhibitors could develop after or in conjunction with chemotherapy [79].…”
Section: Egfr Inhibitorsmentioning
confidence: 99%
“…A phase II study evaluated the clinicopathologic efficacy of erlotinib in patients with stage T2 disease [40]. In this study 20 patients received neoadjuvant erlotinib.…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%